Analysis Of Public Interest In Banking Products - tukma tukma; darwis harahap; ihdi aini; ida royani (Journal Of Sharia Banking, 2021)
This research is based on the fact that there are still many people in Environment I Of Muara Manompas Village, Muara Batang Toru District, not yet familiar with Islamic bank products. The rapid development of Islamic banks has not been able to affect the public interest in products offered by Islamic banks. The entire community of Environment I Muara Manompas Village is Muslim, but public interest in Islamic bank products is still low. This is evidenced by the number of people who prefer products offered by conventional banks rather than Islamic banks. Andri Wicaksono's theory of expressing interest is a tendency that still pays attention to some activities. According to Yudrik Jahja in his book, Educational Psychology interest is an impulse that causes the bonding of individual attention to certain objects such as work, lessons, objects, and people. The sampling technique used is random sampling. Data processing uses SPSS application version 23. Data analysis uses instrument validity and reliability tests, descriptive statistical analysis tests, normality tests, classical assumption tests consisting of multicollinearity tests and heteroskedasticity tests, multiple linear regression tests, and hypothesis tests. The results of this study showed partially the variable of knowledge has an influence on public interest with a value of thitung = 1.841, so thitung ttabel, (1,841 1.66792). Location variables have an influence on people's interests with thitung value = 1.917 so that thitung ttabel (1.917 1.66792) and service quality variables have no effect on public interest with thitung value = 1.172 so thitung ttabel (1,172 1.66792). The results of simultaneous research show that the variables of knowledge, location, and quality of service have an influence on people's interests.